Une économie des émotions - Violaine Roussel (La Nouvelle Revue du Travail)
This article focuses on the emotional work performed by Hollywood talent agents. Intense expressions of emotion pervade the world of entertainment, a complex professional system in which talent representatives play a key role. Far from the “psychologising” explanations and critiques of the emotional pretension that supposedly characterises Hollywood, the article shows that agents’ activity is comprised of relationship work that often takes the form of emotional work. It reveals how such work is learnt in major talent agencies before being performed in the different configurations where production professionals gather. Lastly, it explores the ways in which agents create and maintain strong and intimate ties with artists, as well as the kinds of practical and emotional dilemmas such ties cause the agents.